2012
DOI: 10.1117/1.jbo.17.2.021106
|View full text |Cite
|
Sign up to set email alerts
|

Singlet gradient index lens for deep in vivo multiphoton microscopy

Abstract: Abstract. Micro-optical probes, including gradient index (GRIN) lenses and microprisms, have expanded the range of in vivo multiphoton microscopy to reach previously inaccessible deep brain structures such as deep cortical layers and the underlying hippocampus in mice. Yet imaging with GRIN lenses has been fundamentally limited by large amounts of spherical aberration and the need to construct compound lenses that limit the field-of-view. Here, we demonstrate the use of 0.5-mm-diameter, 1.7-mm-long GRIN lens s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 14 publications
0
63
0
Order By: Relevance
“…Application of the near-infrared high-peak power picosecond pulse laser would improve in vivo two-photon microscopy easily and become a powerful tool to visualize biological phenomena as synaptic conformation changes induced by synaptic plasticity in deeper region of brain. Visualization of all cortical regions and the hippocampus of the living mouse brain will help us to unravel the functions of neural circuits that express synaptic plasticity during learning and memory formation [20,21]. In the future, we hope that these techniques will contribute to fundamental technologies that could be used to reveal intact neural activities at the molecular and cellular levels in the hippocampal area and the basal ganglion and the functional connectome of the living brain.…”
Section: Resultsmentioning
confidence: 99%
“…Application of the near-infrared high-peak power picosecond pulse laser would improve in vivo two-photon microscopy easily and become a powerful tool to visualize biological phenomena as synaptic conformation changes induced by synaptic plasticity in deeper region of brain. Visualization of all cortical regions and the hippocampus of the living mouse brain will help us to unravel the functions of neural circuits that express synaptic plasticity during learning and memory formation [20,21]. In the future, we hope that these techniques will contribute to fundamental technologies that could be used to reveal intact neural activities at the molecular and cellular levels in the hippocampal area and the basal ganglion and the functional connectome of the living brain.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, recent researches incorporating gradient-index (GRIN) lens into nonlinear optical microscopy demonstrated various promising applications in vivo where microscopic images were taken from depths of several millimeters to centimeters under sample surface [45][46][47]. In general, optical fiber was used to deliver excitation light, a miniaturized scanning device was employed to scan the output beam from the optical fiber, and a GRIN lens system was introduced to focus the excitation light into tissues in nonlinear optical endoscope.…”
Section: Discussionmentioning
confidence: 99%
“…74 These properties are comparable to Indium-111 ( 111 In)-oxine, the gold-standard radiotracer for SPECT, which has been successfully used to monitor the migration and localization of CD34+ hematopoietic progenitor cells in rat models of myocardial infarction 75 and stroke. 76 In work by Brenner et al 77 and elsewhere, however, 111 In-oxine has been shown to affect the cellular integrity of hematopoietic progenitor cells. Reduced viability and proliferative capability reduce the potential for translation of this particular radiotracer, since the primary goal of therapeutic stem cells is that they are effective and not that they are of definitive whereabouts.…”
Section: Positron Emission Tomography and Spect: Imaging With Radioacmentioning
confidence: 99%
“…109,110 In addition, the use of microoptical probes with in vivo multiphoton microscopy has now enabled the technique to be used to observe the processes of individual cells. 111 Monitoring stem cell migration with high resolution will be immensely useful in refining cell therapies. So little is currently known about cells posttransplantation; whether cells end up in the brain may ultimately be of little significance to their ability to improve outcome in stroke (although their being dispersed in unknown regions of the recipient would certainly complicate imaging due to, for example, positioning of the coil in MRI).…”
Section: Translating Cell Tracking Technologies To the Clinicmentioning
confidence: 99%